Análise da sobrevida de mulheres com câncer de colo do útero avançado e recorrente/metastático em tratamento com quimioterapia paliativa - VERZARO, Pabline Medeiros (2024)
Objective: To evaluate survival and prognostic factors associated with mortality in women with advanced and recurrent/metastatic cervical cancer undergoing palliative chemotherapy. Method: This retrospective cohort study included 151 women diagnosed with cervical cancer at a High Complexity Oncology Center between January 2020 and December 2022. Participants were divided into two groups: 112 women with advanced disease who received primary treatment with cisplatin or carboplatin weekly (mean age: 53.10 years), and 39 women with recurrent/metastatic disease treated with first- and second-line palliative chemotherapy (cisplatin or carboplatin combined with paclitaxel and gemcitabine every 21 days), with a mean age of 49.05 years. Survival time was measured from the last dose of chemotherapy until death or up to 12 months of survival. Patients who survived beyond this period or were lost to follow-up were considered censored. Kaplan-Meier survival analysis and Cox regression were used to assess overall survival and identify factors associated with mortality. The primary outcome was 12-month survival, while secondary outcomes included overall mean survival and prognostic factors such as ECOG performance status, BMI, Charlson Comorbidity Index, presence of metastasis, additional invasive procedures, symptoms during the last hospitalization, laboratory abnormalities, time to initiation of treatment, and place of death. Results: The advanced disease group showed a significantly higher mean survival (454 days) compared to the recurrent/metastatic disease group, whose mean survival was 300 days (p<0.001). However, the advanced disease group presented more risk factors for mortality, including a Charlson Comorbidity Index < 6, impaired performance status (ECOG 3), Black race, and laboratory abnormalities. Additionally, symptoms related to abdominal surgeries during the last hospitalization, organ dysfunction, and the need for invasive interventions (such as ICU admissions and surgical procedures) were more frequent in this group compared to the recurrent/metastatic disease group.Conclusion: Primary treatment in patients with advanced cervical cancer is associated with longer survival. However, factors such as race, organ dysfunction, and performance status significantly influence mortality. Therefore, it is crucial to adopt an individualized therapeutic approach that balances the benefits of chemotherapy with associated risks and integrates early palliative care to optimize survival and quality of life for these patients.